2022
DOI: 10.3390/polym14153019
|View full text |Cite
|
Sign up to set email alerts
|

Proton-Conducting Biopolymer Electrolytes Based on Carboxymethyl Cellulose Doped with Ammonium Formate

Abstract: In this work, CMC-AFT biopolymer electrolytes system was developed using Carboxymethyl cellulose (CMC) doped with varied amount (10–50 wt.%) of ammonium formate (AFT) in order to study the effect of AFT on the biopolymer-salt system. The chemical structure of the biopolymer was studied using Fourier-Transform infrared (FTIR) and X-ray diffraction (XRD). The interaction between the COO− of CMC and the weakly-bound H+ of NH4+ AFT occurred at 1573 cm−1 as seen in FTIR analysis and the amorphous phase was found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…69 Table 3 shows a comparison of the ionic conductivity obtained in this work with the ionic conductivity obtained from previous work. The highest ionic conductivity obtained in this work, that is, CMC/CMCh (80/20) + 20 wt% LiOAc was compared with the other optimum ionic conductivity reported in some previous research such as CMC + 35 wt% DTAB, 10 CMC + 25 wt% NH 4 Br, 60 CMC + 50 wt% AFT, 61 CMC/PVA + 6 wt% NH 4 Cl, 62 CMC/PVA + 6 wt% NH 4 Cl, 62 MC + NH 4 NO 3 + PEG, 63 and PVA + LiClO 4 + TiO 2 . 64 Based on the comparison, it can be stated that SPE membranes of CMC/CMCh (80/20) with various weight percentages of LiOAc have higher potential contributing conductivity.…”
Section: Ionic Conductivity Analysissupporting
confidence: 47%
“…69 Table 3 shows a comparison of the ionic conductivity obtained in this work with the ionic conductivity obtained from previous work. The highest ionic conductivity obtained in this work, that is, CMC/CMCh (80/20) + 20 wt% LiOAc was compared with the other optimum ionic conductivity reported in some previous research such as CMC + 35 wt% DTAB, 10 CMC + 25 wt% NH 4 Br, 60 CMC + 50 wt% AFT, 61 CMC/PVA + 6 wt% NH 4 Cl, 62 CMC/PVA + 6 wt% NH 4 Cl, 62 MC + NH 4 NO 3 + PEG, 63 and PVA + LiClO 4 + TiO 2 . 64 Based on the comparison, it can be stated that SPE membranes of CMC/CMCh (80/20) with various weight percentages of LiOAc have higher potential contributing conductivity.…”
Section: Ionic Conductivity Analysissupporting
confidence: 47%
“…The polar sites namely carboxymethyl group (À CH 2 COO À ) of CMC, methoxyl group (À OCH 3 ) of MC, and also hydroxyl group (À OH) of cellulose/ cellulose derivatives. [45,59,61] Previous work [40] NaCMC/PVA (80/20) À 30 % NaI 2.52 × 10 À 3 Previous work [45] CMC + LiPF 6 (1 M) 4.8 × 10 À 5 Previous work [62] 2 wt% CMC + 20 wt% LiClO 4 + 10 wt% CA 1.24 × 10 À 7 Previous work [63] CMC + 35 % DTAB 7.72 × 10 À 4 Previous work [64] CMC + 25 % NH 4 Br 1.12 × 10 À 4 Previous work [65] CMC/50 % AFT 1.47 × 10 À 4 Previous work [66] CMC/PVA-6 % NH 4 Cl 8.86 × 10 À 5 Previous work [67] ChemistrySelect Functional groups studies of the biopolymer electrolyte membrane respectively. [68] MC/CMC (80/20)-based polymer host shows the OÀ H group stretching vibration absorption at 3446 cm À 1 .…”
Section: Ionic Conductivities and Li-ion -Polymer Host Interaction Me...mentioning
confidence: 99%
“…Much previous research revealed this mechanism known as ions hopping or ions migration 14,66 . The anion of lithium salt was also proposed coordinating to hydrogen atom of the polymer chain 49,67 …”
Section: Resultsmentioning
confidence: 98%
“…14,66 The anion of lithium salt was also proposed coordinating to hydrogen atom of the polymer chain. 49,67…”
Section: Ionic Conductivity Analysismentioning
confidence: 99%